THE ROLE OF LEGAL AUDIT IN MITIGATION OF THE RISK OF BANKRUPTCY OR PKPU APPLICATIONS TOWARDS THE COMPANY - Aprita, Serlika; Iwari, Dian Puspa; Febryani, Evy (JILPR Journal Indonesia Law and Policy Review, 2025)
Several well-known companies have recently been the subject of discussion due to their bankruptcy filings. One of the most frequently filed disputes is a request for a suspension of debt payment obligations (PKPU) and bankruptcy. At least several companies have disputes being processed at the Commercial Court at the Central Jakarta District Court (PN). One such case occurred with the Meikarta developer, PT Mahkota Sentosa Utama (MSU), which was sued by PT Graha Megah Tritunggal for a suspension of debt payment obligations (PKPU) or bankruptcy on October 6, 2020, under case number 328/Pdt.Sus-PKPU/2020/PNNiagaJkt.Pst. Based on the cases above, bankruptcy can occur due to a bankruptcy lawsuit. This condition reflects a high level of financial distress for the company. This can occur due to the inability of company management to carry out its management functions, thus threatening business continuity. In other words, corporate governance is not running as it should. The type of research used in this paper is normative legal research. An important step in legal risk management, legal audits have a strategic role in mitigating potential bankruptcy applications or PKPU against companies by helping to detect the risk of corporate bankruptcy early. Legal audit results are often considered an important tool to support a company's defense in legal proceedings, including in bankruptcy applications or PKPU. Investigative legal audit results can be used as evidence of expert testimony in criminal trials. The Board of Commissioners and the Audit Committee as internal monitoring mechanisms have a role to detect potential bankruptcy early. Therefore, an external monitoring role is needed, carried out by an independent auditor, in this case a public accounting firm (KAP). Because auditing can provide value and benefits to a company's decision makers regarding the quality of the company's financial report information, the role of audits can detect the possibility of a company's bankruptcy.